Antioxidant and immunoregulatory activity of polysaccharides from adzuki beans (Vigna angularis). (November 2015) - Yao, Yang; Xue, Peng; Zhu, Yingying; Gao, Yue; Ren, Guixing
Abstract: Water-extractable and alkali-extractable polysaccharides from the seed of adzuki beans and their three polysaccharide sub-fractions were isolated and purified by anion-exchange and gel filtration chromatography. AWP-1 and AWP-2 were composed of Rha, Ara, Man, Gal and Glu. AAP-1 was composed of Rha, Ara, Man, Gal and GalA. The antioxidant and immunoregulatory activities of the polysaccharides were evaluated. The results indicated that AWP-1, AWP-2, and AAP-1 had significant antioxidant and immunoregulatory activities. The results suggest that AWP-1, AWP-2, and AAP-1 have therapeutic implications in the treatment of inflammation and inflammatory-related disease. Highlights: Three polysaccharide sub-fractions were isolated and purified from adzuki beans. Their structural features were analyzed using FT-IR and HPSEC-MALLS-RID. The polysaccharide sub-fractions have antioxidant and immunoregulatory activities.